Activity of the UNR Military and Sanitary Mission on prisoners’ of war affairs in Germany (1919) - Maciej Krotofil; Ihor Sribnyak; Мilana Sribniak (Cхід)
The relevance of the article lies in the necessity to discover major aspects of the UNR Military and Sanitary Mission’s activity on prisoners of war (POWs) in Germany. The Mission’s crucial task was to facilitate their repatriation. It should be noted that the main obstacle for Ukrainian POWs’ transportation was based on the development of the destructive political processes on the territory of former Russian empire, particularly due to the consolidation of power in the hands of Bolsheviks in Petrograd. The study is to determine the features of the cooperation between the Mission and Ukrainian POWs’ camp communities, as well as the quantity and characteristics of the humanitarian assistance provided to POWs. The research identifies that the Mission succeeded in improving living conditions for POWs at camps through sending food supplies, clothes and shoes. In addition, it cared for POWs’ moral needs by implementing courses, lessons, theatrical plays and sending Ukrainian periodicals and books to the camps. What is more, the Mission was responsible for the sanitary care, especially in regard to sending medicaments and medical staff. The mission also developed the ways and logistics of POWs’ repatriation process as well. The study’s novelty lies in in a comprehensive research of the Mission’s activity which resulted in organizing, in September-October 1919, the transportation of small POWs group to Czechoslovakia with Ukraine as a final destination. Nonetheless, the negotiations regarding a massive repatriation were not successful and, thus, a considerable part of POWs stayed in camps until May 1920. Despite these events, the Mission’s activity had positive consequences for most Ukrainian POWs, particularly organizing their national life in camps.